1987
DOI: 10.1210/endo-121-1-36
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins Affect the Central Nervous System to Produce Hyperglycemia in Rats*

Abstract: The influence of prostaglandins (PG) on central nervous system regulation of blood sugar homeostasis was studied in rats. Substances were injected into the third cerebral ventricle of anesthetized rats while rectal temperature and hepatic venous plasma glucose concentration were recorded. Stereotaxic microinjection of PGD2, E1, E2, and F2 alpha produced hyperglycemia and hyperthermia. The relative order of potency in hyperglycemia, PGF2 alpha greater than D2 greater than E1 greater than E2, was not consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…However, information about the effects of PGs on glucose metabolism in vivo is limited. It has been documented that PGs have a modulating effect on norepinephrine (NE) release at nerve endings in the central nervous system [7]. In streptozo-tocin-induced diabetic rats (STZ-diabetic rats), an insulin-dependent diabetes mellitus (IDDM)-like model, a 1 -adrenergic activation can lower plasma glucose via endogenous b-endorphin [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, information about the effects of PGs on glucose metabolism in vivo is limited. It has been documented that PGs have a modulating effect on norepinephrine (NE) release at nerve endings in the central nervous system [7]. In streptozo-tocin-induced diabetic rats (STZ-diabetic rats), an insulin-dependent diabetes mellitus (IDDM)-like model, a 1 -adrenergic activation can lower plasma glucose via endogenous b-endorphin [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, high-dose PGE 1 administration caused hyperglycemia in the HighPG group. Direct PGE 1 injection into the third cerebral ventricle has been reported to produce hyperglycemia in rats [19]. Because PGE 1 is transported across the blood-brain barrier [20], there is a possibility that the high dose of PGE 1 administered in this study resulted in an elevated brain PGE 1 concentration, leading to hyperglycemia.…”
Section: Discussionmentioning
confidence: 73%
“…We previously reported that PGF2a-induced hyper glycemia results from epinephine secretion from the adre nal medulla [1], The increased epinephrine secretion in duced by PGF2C X was significantly suppressed by pyril amine and diphenhydramine, but not by ranitidine.…”
Section: Discussionmentioning
confidence: 89%
“…In the first experiment, when PGF2« (50 p g /p l saline) or I pi saline was injected into the third cerebral ventricle as previously de scribed [1] with or without diphenhydramine, pyrilamine or rani- In the second experiment, when PGFict (50 p g /p l saline) or I ul saline was injected into the third cerebral ventricle with or without diphenhydramine, pyrilamine or ranitidine (5 x 10~8 m o l/p l saline), hepatic venous plasma epinephrine levels were determined using high-performance liquid chromatography with an electrochemical detector as previously described [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation